Rule breaking mediates the developmental association between GABRA2 and adolescent substance abuse. (9th May 2014) - Trucco, Elisa M.; Villafuerte, Sandra; Heitzeg, Mary M.; Burmeister, Margit; Zucker, Robert A.
<x xml:space="preserve">Abstract</x> Background This study's primary aim was to examine age‐specific associations between GABRA2, rule breaking, problematic alcohol use, and substance abuse symptomatology. The secondary aim was to examine the extent to which rule breaking mediates the GABRA2‐substance abuse relationship. Methods A sample (n = 518) of primarily male (70.9%) and White (88.8%) adolescents from the Michigan Longitudinal Study was assessed from ages 11–18. Age‐specific effects of GABRA2 on rule breaking, problematic alcohol use, and substance abuse symptomatology were examined using nested path models. The role of rule breaking as a mediator in the association between GABRA2 and substance abuse outcomes was tested using prospective cross‐lagged path models. Results GABRA2 is significantly (p < 0.05) associated with rule breaking in mid‐ to late‐adolescence, but not substance abuse symptomatology across adolescence. GABRA2 effects on problematic alcohol use and substance abuse symptomatology operate largely (45.3% and 71.1%, respectively, p < 0.05) via rule breaking in midadolescence. Conclusions GABRA2 represents an early risk factor for an externalizing pathway to the development of problematic alcohol and drug use.